2003
DOI: 10.1002/anie.200351002
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Inversion as a Diastereomeric Relay in Azasugar Synthesis: The First Synthesis of Adenophorine

Abstract: A temperature‐dependent relay of chirality is based on the inversion of the nitrogen lone pair in cyclic azasugars. Elimination from the conformation preferred at a given temperature leads to a cyclic imine, and in a subsequent nucleophilic attack the stereochemical information is relayed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 52 publications
4
30
0
Order By: Relevance
“…Four years after the publication of the (-)-adenophorine synthesis by Maughan and co-workers, [13] we have performed the first total synthesis of naturally occurring (+)-adenophorine in 14 steps from the Garner's aldehyde enantiomer and in 3.5 % overall yield. We have once again exploited the synthetic potential of the trans-2,6-disubstituted 1,2,5,6-tetrahydropyridine key intermediate for the preparation of enantiomerically pure α-1-C-alkyl-iminosugars.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Four years after the publication of the (-)-adenophorine synthesis by Maughan and co-workers, [13] we have performed the first total synthesis of naturally occurring (+)-adenophorine in 14 steps from the Garner's aldehyde enantiomer and in 3.5 % overall yield. We have once again exploited the synthetic potential of the trans-2,6-disubstituted 1,2,5,6-tetrahydropyridine key intermediate for the preparation of enantiomerically pure α-1-C-alkyl-iminosugars.…”
Section: Discussionmentioning
confidence: 98%
“…The absolute configuration of this (+)-iminosugar, isolated from Adenophora spp. by Ikeda and co-workers in 2000, [8] was determined three years later by optical rotation measurements performed on the (-) enantiomer synthesized by Davis et al [13] Iminosugars are frequently synthesized from carbohydrates as chiral pool starting materials with use of an amination-intermolecular cyclization sequence or an intramolecular reductive amination cyclization as the key step.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that regioselective dehydrochlorination of N-chloropiperidine azasugars is controlled by the switchable configuration at the chloramine nitrogen atom. 53 The importance of detailed mechanistic and stereochemical insights in dehydrochlorination reactions has also been shown in the case of N-chlorinated macrolide antibiotics.…”
Section: -52mentioning
confidence: 97%
“…The first synthesis of (-)-adenophorine (6) [7] (nonnatural enantiomer) was achieved in 26 % yield in ten steps from the d-glucose derivative 114 by Davies et al [59] using an intramolecular Staudinger/aza-Wittig reaction, as presented in Scheme 14. The opposite optical rotation of the synthetic compound allowed the authors to assign the absolute configuration of natural (+)-adenophorine.…”
Section: Chiral-pool Starting Materials: Carbohydratesmentioning
confidence: 99%